Girl, forgotten : a novel - Slaughter, Karin, 1971- (William Morrow, an imprint of HarperCollinsPublishers, 2022)
Who killed Emily Vaughn? The stunning new standalone thriller from international No. 1 bestseller Karin Slaughter. A girl with a secret ... Longbill Beach, 1982. Emily Vaughn gets ready for prom night, the highlight of any high school experience. But Emily has a secret. And by the end of the evening, she will be dead. A murder that remains a mystery ... Forty years later, Emily's murder remains unsolved. Her friends closed ranks, her family retreated inwards, the community moved on. But all that's about to change. One final chance to uncover a killer ... Andrea Oliver arrives in town with a simple assignment: to protect a judge receiving death threats. But her assignment is a cover. Because, in reality, Andrea is here to find justice for Emily - and to uncover the truth before the killer decides to silence her too--